Western influenced Filipino music [videorecording] - National Commission for Culture and the Arts (Quezon City : Felta.)
A television program on the Filipinization of spanish and American musical influences features on the orchestra and the Filipino classical music.
Keywords: Music -- Philippines -- Western influences